Aging effect on high heat dissipation DBA and DBAC substrates for high power electronics. Issue 19 (1st October 2022) - Chen, Guan-Ren; Lin, Kun-Lin; Lin, Chien-Cheng
Abstract: Direct bonded aluminum (DBA) and direct bonded aluminum with copper (DBAC) substrates were fabricated successfully by transient liquid phase bonding. The 300 nm Ni metallization was deposited on the surface of AlN and joined with Al and Cu to form the DBA and DBAC substrates. After bonding, the discontinuous Al9 (Fe, Ni)2 and Al3 Ni intermetallic composites (IMCs) were formed at the interface of DBA substrate due to the diffusion of impurities (Fe) in Al and Ni metallization of AlN. As for DBAC substrate, three continuous Al4 Cu9, AlCu, and Al2 Cu IMCs were formed at the Cu/Al interface. After isothermal aging to 250 °C/2000 h, the bonding area of DBA and DBAC was greater than 98% and the interfacial shear strength of DBA was measured as 40 MPa and the DBAC decreased to 12.5 MPa due to the brittle Al–Cu IMCs at the Al/Cu interface. The unprotected Cu oxide and micrometers size cracks were formed at the surface of Cu in DBAC but no obvious Al oxide and crack in DBA. Even though the thermal conductivity of DBAC is 199 W/mK higher than DBAC substrates (184 W/mK) at room temperature, the thermal stability of DBA is better than DBAC for the applications in high-power electronics.